Climate resilience in displacement: Examining UNHCR’s SuLMER intervention in Cox’s Bazar, Bangladesh - Vaselli, Alessandra; Khalid, Shahab; Savelli, Adam; Craparo, Alessandro; Basel, Ashleigh; Minoarivelo, Henintsoa Onivola; Tsoka, Jonathan; Dao, Hoa; Ma, Suza; Nipul, Barua; Hoque, Ehsanul; Sarma, Santanu; et al. (2025)
This Policy Brief was prepared for presentation at COP 30 in Belém, Brazil. For a fuller accounting of the research, please see the Summary Guidance Note or Full Report.